2004
DOI: 10.1021/jf030461e
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, Low Molecular Weight Carbohydrates, and Total Antioxidant Capacity in Strawberries (Fragaria × ananassa):  Effects of Cultivar, Ripening, and Storage

Abstract: Four cultivars of strawberries (Senga Sengana, BFr77111, Elsanta, and Honeoye) were studied for their content of antioxidants, total antioxidant capacity, and low molecular weight carbohydrates in relation to harvest year, ripening stage, and cold storage. For ascorbic acid, chlorogenic acid, ellagic acid, and total antioxidative capacity, measured in both water-soluble and water-insoluble extracts, there was a 2-5-fold variation among cultivars. Unripe berries contained lower concentrations of chlorogenic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
4
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 37 publications
17
113
4
3
Order By: Relevance
“…Moreover, strawberries are economically and commercially important and widely consumed fresh or in processed forms, such as jams, juices, and jellies by their sweet taste and potential benefits to the health (Giampieri et al, 2012). And, by their antioxidant activity, they are important in the prevention of certain types of cancers, as well as, anti-inflammatory functions, cardiovascular, obesity and other chronic diseases (Basu et al, 2009;Crecente-Campo, Nunes-Damaceno, Romero-Rodríguez, & Vázquez-Odériz, 2012;Giampieri et al, 2012;Hannum, 2004;Olsson et al, 2004;Oszmiański et al, 2009). It is established that oxidation processes are involved in various chronic and degenerative diseases and that the intake of chemical constituents with antioxidant activity, found in plants in high concentrations, has beneficial effects on health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, strawberries are economically and commercially important and widely consumed fresh or in processed forms, such as jams, juices, and jellies by their sweet taste and potential benefits to the health (Giampieri et al, 2012). And, by their antioxidant activity, they are important in the prevention of certain types of cancers, as well as, anti-inflammatory functions, cardiovascular, obesity and other chronic diseases (Basu et al, 2009;Crecente-Campo, Nunes-Damaceno, Romero-Rodríguez, & Vázquez-Odériz, 2012;Giampieri et al, 2012;Hannum, 2004;Olsson et al, 2004;Oszmiański et al, 2009). It is established that oxidation processes are involved in various chronic and degenerative diseases and that the intake of chemical constituents with antioxidant activity, found in plants in high concentrations, has beneficial effects on health.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro oxidation assays showed that the antioxidant activity of strawberries has been directly correlated with anthocyanin content in the fruit (Andersen, Fossen, Torskangerpoll, Fossen, & Hauge, 2004). However, this content is affected by the cultivar, ripening stage, storage conditions and their post-harvest treatment (Crecente-Campo et al, 2012;Olsson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cardinal had a higher rate of vitamin C accumulation when fruit reached its fully maturity. Olsson et al (2004), and Kafkas et al (2007) also reported that ascorbic acid concentration was generally higher in ripe berries compared to unripe ones.…”
Section: Chemical Analysismentioning
confidence: 89%
“…Storage (48C for 72 h) of strawberries reduced the content of p-coumaric and chlorogenic acids from 74 to 58 lmol/100 g FW and from 440 to 320 lmol/kg FW, respectively [63]. The content of cinnamic acid derivatives in the flesh of strawberries expressed as chlorogenic acid was not affected by freezedrying [64].…”
Section: Structures Of Individual Compounds Content and Changes In Cmentioning
confidence: 92%
“…The following list gives an enumeration of all the measures or procedures investigated: Maturity, ripening and time of harvest [63,74,82,99,115,116,176,178,179,188,189,194] 58,112,142,162,181,191,196], differentiation in fractions [114,167,174], peeling [109,142,153,180], special pressing or extraction [2, 64,72,165], enzymatic treatment and maceration [51], irradiation [53,158,175,183], drying [8,102,132,152,159], sensory effects [51], germination [88], browning-blanching and polyphenoloxidase (PPO) activity [124], proveniences [8,12,63,107,110,112,…”
Section: Aspects Of Postharvest Processing and Storage Proceduresmentioning
confidence: 99%